Alat Pencacah Plastik Lunak Untuk Membantu Produksi Ecobrick - Edi Purwanto; Umi Fadilah; Fajar Suryawan; Ratnasari Nur Rohmah (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2020)
Every year the use of plastic is always increasing. This causes plastic pollution everywhere. In order to decrease the plastic pollution, a recycling system is needed. Currently, several groups of people have created Ecobrick. Ecobrick is a waste recycling system that utilizes PET (Polyethylene Therepthalate) bottles filled with plastic scraps. To facilitate the cutting, a plastic chopper was created. This tool is designed with a chopper blade unit driven by a single phase induction motor. For transmission between motors to the blades used gears and chains. This tool is also equipped with an ultrasonic sensor and Arduino as a control. If the sensor detects that the plastic is inserted, the sensor will send data to be processed by Arduino, so the relay will activate the motor for 20 seconds, until the plastic is completely chopped. In order to know how long for all one plastic chopped, several experiments have been carried out. For power supply, each circuit uses two output adapters of 5 VDC and 9 VDC.